A new megaflora from the Huancané Formation (Lower Cretaceous), Peru - Martinez, Leandro Carlos Alcides (2016)
The Cretaceous flora of Peru has received little interest. In this communication we present new fossil remains from the Huancané Formation (Lower Cretaceous). The fossil plants are very well preserved and come from a single locality with three different stratigraphic levels close to Cusco city. The fossil flora is dominated by Brachyphyllum Brongniar, Cupressinocladus Seward and leaves and seeds assigned to the Araucariaceae. The rest of the assemblage consists of ferns and putative pteridosperms, such as Cladophlebis Brongniart and Weichselia Stiehler. In addition, scarce and disperse pinnae of Sagenopteris? Presl and Sphenopteris Sternberg were also recorded. The presence of Weichselia is interesting, because this taxon has a worldwide distribution mainly in Cretaceous strata, and supports the age inferred to the Huancané Formation based on sedimentological and palynological studies. Therefore, the plant assemblage would suggest a forest canopy dominated by conifers, with an understory composed by ferns (Cladophlebis, Sphenopteris and Weichselia) and pteridosperms (Sagenopteris). This flora would have developed in a warm and humid climate during the deposition of the Huancané Formation. These new data contribute to the fossil record of South America,and particularly to the Cretaceous flora near equatorial regions.